Identifikasi Kebutuhan Rencana Pembangunan Sentra Industri Kota Tangerang Selatan - Candra, Fitria (Sumatera Research, 2018)
ABSTRACT          The purpose of this research is to identify the need of development plan of Small and Medium Industry in South Tangerang City by constructing Small and Medium Industry Center by using data of small and medium industry of South Tangerang City that exist in Industry and Trade Office of South Tangerang City. Development of Industrial Centers in a region must meet the criteria that is 1. Local government to provide at least 5,000 m2 of land in the appropriate location RTRW and deserve topography for physical development equipped with document of legality of land ownership by local government and also have supporting infrastructure to central location (road and electricity ). 2. Having the IKM Sentral Development Pattern (Masterplan, Institutional Pattern and Business Plan), 3. Having the DED document for the construction of Sentra IKM and Wastewater Treatment Installation (IPAL), 4. Preparing the AMDAL / UKL / UPL, 5. The SMI product has prospects to be developed in terms of market potential, availability of raw materials and availability of human resources. 6. A statement of willingness from at least 20 SMEs to be relocated or newly established SMEs to new IKM centers. 7. Statement Letter of Regional Government is willing to establish a management institution authorized by the Related Institution / Notary 8. Statement Letter of Regional Government willing to provide operational cost for institutional and sustainability of the center.          The results of this study are the type of Small and Medium Industries that can be developed into Industrial Sentra Tangerang City South is the Food and Beverage Industry Center in each District in the City of South Tangerang, Sentra Chemical Industry and goods from chemicals in Setu Subdistrict, Sentra Industri Pakaian Jadi in Kecamatan Pondok Aren.. Keywords : Small and Medium Industry, Small and Medium Industry Center   ABSTRAK          Tujuan dari penelitian ini adalah untuk mengidentifikasi kebutuhan rencana pengembangan Industri Kecil dan Menengah di Kota Tangerang Selatan dengan membangun Sentra Industri Kecil dan Menengah dengan menggunakan data industri kecil dan menengah Kota Tangerang Selatan yang ada di Dinas Perindustrian dan Perdagangan Kota Tangerang Selatan. Pembangunan Sentra Industri di suatu daerah harus memenuhi kriteria yaitu 1. Pemda menyediakan lahan minimal 5.000 m2 berada di lokasi yang sesuai RTRW dan layak secara topografi untuk pembangunan fisik dilengkapi dengan dokumen legalitas kepemilikan lahan oleh Pemda serta mempunyai infrastruktur penunjang menuju lokasi sentra (jalan dan listrik). 2. Memiliki Pola Pengembangan Sentra IKM (Masterplan, Pola Kelembagaan dan Bisnis plan), 3. Memiliki dokumen DED pembangunan Sentra IKM dan Instalasi Pengolah air limbah (IPAL), 4. Menyusun  AMDAL/UKL/UPL, 5. Produk IKM-nya mempunyai prospek untuk dikembangkan dilihat dari potensi pasar, ketersediaan bahan baku dan ketersediaan sumber daya manusia. 6. Surat pernyataan kesediaan dari minimal 20 IKM untuk direlokasi atau IKM yang baru berdiri ke sentra IKM yang baru. 7. Surat pernyataan Pemda bersedia membentuk kelembagaan pengelola yang disahkan oleh Instansi Terkait/Notaris 8. Surat pernyataan Pemda bersedia menyediakan biaya operasional bagi kelembagaan dan keberlanjutan sentra.          Hasil penelitian ini adalah jenis Industri Kecil dan Menengah yang dapat dikembangkan menjadi Sentra Industri Kota Tangerang Selatan adalah Sentra Industri Makanan dan Minuman di setiap Kecamatan di Kota Tangerang Selatan, Sentra Industri Kimia dan barang-barang dari bahan kimia di Kecamatan Setu,  Sentra Industri Pakaian Jadi di Kecamatan Pondok Aren. Kata kunci: Industri Kecil dan Menengah, Sentra Industri Kecil dan Menengah.